2021
DOI: 10.1002/admt.202100790
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing of Shape‐Memory Semi‐Interpenetrating Polymer Networks Based On Aromatic Heterochain Polymers

Abstract: advent of smart materials. These materials are called smart due to their self-sensing, self-adaptability, memory capabilities and manifold functions. [1,2] Smart materials are capable of transforming their physical properties (dimensions, shape, stiffness, viscosity, adhesion, and color) following the action of different stimuli, namely, temperature, mechanical strength, electric current, light, magnetic field, chemicals, etc. [3][4][5] A combination of smart materials and 3D printing has resulted in a new fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…DMA results demonstrate that aliphatic PBIs show facile phase switching, which is important for the appearance of the shape-memory effect [ 35 ]. Similar results were observed in our previous work on shape-memory PBI-based materials [ 25 , 26 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…DMA results demonstrate that aliphatic PBIs show facile phase switching, which is important for the appearance of the shape-memory effect [ 35 ]. Similar results were observed in our previous work on shape-memory PBI-based materials [ 25 , 26 ].…”
Section: Resultssupporting
confidence: 91%
“…However, traditional PBIs such as poly-2,2′- m -phenylene-5,5′-dibenzimidazole have highly rigid backbones and do not contain any flexible groups, so they do not possess a shape-memory effect. Previously, we showed that high-temperature SMPs could be obtained from semi-interpenetrating polymer networks based on fully aromatic poly-2,2′- p -oxydiphenylene-5,5′-dibenzimidazole (OPBI) [ 25 ]. In [ 26 ], we showed that a PBI with flexible aliphatic octamethylene fragments possesses good shape-memory ability, in contrast to poly (imide- co -benzimidazole) [ 27 ] or OPBI [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…), heterogenization enables tailoring specific photopolymer characteristics, including optical 251 and electrical properties, 309 data storage, 310 electromagnetic absorption, 311 and shape memory. 115,312 This further emphasizes the importance of heterogenization in jewelry and decoration, dentistry, electronics, and robotics applications. 5,219,313 Stimuli-responsive polymers are a prominent example of advanced materials that can change their properties or behavior in response to specific external conditions or triggers.…”
Section: Applicationsmentioning
confidence: 93%
“…Apart from the significant effect of improved toughening on usability in different industries (aerospace, automotive, medicine, etc. ), heterogenization enables tailoring specific photopolymer characteristics, including optical and electrical properties, data storage, electromagnetic absorption, and shape memory. , This further emphasizes the importance of heterogenization in jewelry and decoration, dentistry, electronics, and robotics applications. ,, …”
Section: Applicationsmentioning
confidence: 98%
“…There are approaches to obtain biocompatible materials by modification of implantable polyimide films [29] and polyimide covalent organic frameworks for drug delivery applications [30]. Photosensitive compositions based on aromatic heterochain polymers and reactive solvents can be used to form mechanically durable threedimensional objects by laser stereolithography [31,32], digital light processing (DLP) [33,34], and liquid crystal display (LCD) [35,36] 3D printing.…”
Section: Introductionmentioning
confidence: 99%